Non-aqueous electrolyte and secondary battery

CN122696801APending Publication Date: 2026-09-04SHENZHEN CAPCHEM TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510251181.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-04
Publication Date
2026-09-04

AI Technical Summary

Technical Problem

[0003]针对现有含有有机过氧化物或偶氮化合物的非水电解液在存储过程中易变质的问题,本发明提供了一种非水电解液及二次电池

Benefits of technology

[0014] According to the non-aqueous electrolyte provided by the present invention, compounds shown in structural formula 1 and/or structural formula 2 are added as first additives. The first additives can participate in the formation of a solid electrolyte interfacial film on the surface of the positive and negative electrodes, making the solid electrolyte interfacial film more dense and stable. This solid electrolyte interfacial film can provide better protection for the positive and negative electrodes and the non-aqueous electrolyte, and improve the cycle stability of the battery. However, the inventors have found that during long-term storage, organic peroxides and azo compounds can lead to an increase in the acidity and color of the electrolyte, deteriorating the quality of the electrolyte and affecting its application in lithium-ion batteries. This is because the first additives will produce alcohols containing active hydrogen during high-temperature storage, resulting in poor weather resistance and deterioration of electrochemical performance of the non-aqueous electrolyte. To solve this problem, compounds shown in structural formula 3 are further added to the non-aqueous electrolyte as second additives. The second additives have high reaction selectivity for active hydrogen, which can reduce the effect of water in the electrolyte system and active hydrogen contained in the positive and negative electrodes, indirectly reducing the problems of lithium salt decomposition and acidity increase caused by active hydrogen. Therefore, combining these two additives in a certain proportion can improve the weather resistance of non-aqueous electrolytes, inhibit the increase of acidity and color during storage, and at the same time take into account the room temperature cycle performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122696801A_ABST
    Figure CN122696801A_ABST
Patent Text Reader

Abstract

In order to overcome the problem that the existing non-aqueous electrolyte containing organic peroxide or azo compound is easy to deteriorate during storage, the application provides a non-aqueous electrolyte, which comprises a non-aqueous organic solvent, an electrolyte salt and an additive, the additive comprises a first additive and a second additive, the first additive comprises a compound shown in structural formula 1 and / or a compound shown in structural formula 2, and the second additive comprises a compound shown in structural formula 3; structural formula 1 structural formula 2 structural formula 3. Meanwhile, the application also discloses a secondary battery comprising the above non-aqueous electrolyte. The non-aqueous electrolyte provided by the application can improve the weather resistance of the non-aqueous electrolyte, inhibit the increase of acidity and color during storage, and also consider the normal temperature cycle performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of battery material technology, specifically relating to a non-aqueous electrolyte and a secondary battery. Background Technology

[0002] In cutting-edge technological research, high energy density and long cycle life of lithium-ion batteries have always been a common goal pursued by the industry. One of the keys to long cycle life technology lies in adjusting and optimizing the electrochemical stability of the solid electrolyte interphase (SEI) through electrolyte design. However, the SEI formed by existing conventional additives has defects. During charge and discharge, it continuously dissolves and reorganizes, which not only thickens the interfacial film and increases impedance, but also consumes active materials, leading to capacity decay. Organic peroxides and azo compounds are generally used as initiators of gel electrolytes in secondary batteries and are consumed before the battery's first charge-discharge formation. However, there are also reports of their use as electrolyte additives. Due to the high chemical reactivity of these two types of substances, they can easily disrupt the balance of the electrolyte system, thereby affecting battery performance. Therefore, the potential quality risks cannot be ignored. Summary of the Invention

[0003] To address the problem that existing non-aqueous electrolytes containing organic peroxides or azo compounds are prone to deterioration during storage, this invention provides a non-aqueous electrolyte and a secondary battery.

[0004] The technical solution adopted by the present invention to solve the above-mentioned technical problems is as follows: On one hand, the present invention provides a non-aqueous electrolyte comprising a non-aqueous organic solvent, an electrolyte salt, and an additive, wherein the additive comprises a first additive and a second additive, the first additive comprising a compound represented by structural formula 1 and / or a compound represented by structural formula 2, and the second additive comprising a compound represented by structural formula 3. Structural Formula 1 Wherein, n is 0 or 1; R1 and R2 are each independently selected from hydrogen, substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C1-C12 acyl, substituted or unsubstituted C2-C12 alkoxyacyl, and substituted or unsubstituted C2-C12 ether; and R1 and R2 do not... Both are hydrogen, and R1 and R2 can be linked together to form a ring or not; R3 is selected from substituted or unsubstituted C1-C12 alkylene groups, substituted or unsubstituted C2-C12 alkenyl groups, substituted or unsubstituted C2-C12 alkyne groups, substituted or unsubstituted C6-C20 aryl groups, and substituted or unsubstituted C2-C12 ether groups; when R1, R2, and R3 are substituted, the substituents are alkoxy, hydroxyl, acyl, ester, cyano, or halogen. Structural Formula 2 R4 and R5 are each independently selected from substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C2-C6 alkenyl, substituted or unsubstituted C2-C6 alkynyl or substituted or unsubstituted C1-C6 alkyl hydroxyl groups, and R4 and R5 are linked together to form a ring or not; R6 is selected from hydrogen, substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C2-C6 alkenyl or substituted or unsubstituted C2-C6 alkynyl, C1-C6 cyano, C2-C6 ester, substituted or unsubstituted C2-C6 amide or substituted or unsubstituted C1-C6 amidine; Structural Formula 3 Wherein, m is selected from 1 to 4; R7 is selected from substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C1-C12 silyl, substituted or unsubstituted C0-C8 phosphoryl, substituted or unsubstituted C1-C10 sulfonyl.

[0005] Optionally, the compound represented by structural formula 1 satisfies at least one of the following conditions: (1) R1 is selected from hydrogen, and R2 is selected from hydrogen. substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl, wherein R 10 Selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, substituted or unsubstituted C2-C11 alkynyl, and substituted or unsubstituted C6-C20 aryl; (2) R1 and R2 are each independently selected from substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, or substituted or unsubstituted C6-C20 aryl. (3) R1 is selected from R2 is selected from substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl, or... , where R 11 Selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, substituted or unsubstituted C2-C11 alkynyl, substituted or unsubstituted C6-C20 aryl, and substituted or unsubstituted C2-C12 ether. (4) R1 is selected from , where R 12 R2 is selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, and substituted or unsubstituted C2-C11 alkynyl; R2 is selected from hydrogen, substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, and substituted or unsubstituted C6-C20 aryl or... , where R 13 Selected from substituted or unsubstituted C1-C11 alkyl groups, substituted or unsubstituted C2-C11 alkenyl groups, and substituted or unsubstituted C2-C11 alkynyl groups.

[0006] Optionally, the compound represented by structural formula 1 includes one or more of the following compounds: .

[0007] Optionally, the compound represented by structural formula 2 satisfies at least one of the following conditions: (1) When R4 and R5 are substituted, the substituents are carboxyl, hydroxyl, halogen or cyano; when R6 is substituted, the substituents are hydroxyl, halogen or alkoxy. (2) R6 is selected from cyano; (3) R4 and R5 are each independently selected from substituted or unsubstituted C1-C6 alkyl groups.

[0008] Optionally, the compound represented by structural formula 2 includes one or more of the following compounds: .

[0009] Optionally, the compound represented by structural formula 3 includes one or more of the following compounds: .

[0010] Optionally, the non-aqueous electrolyte satisfies at least one of the following conditions: (1) The mass content X of the first additive is 10~5000 ppm based on the total mass of the non-aqueous electrolyte; (2) The mass content Y of the second additive is 10~1000ppm based on the total mass of the non-aqueous electrolyte; (3) The mass content X of the first additive and the mass content Y of the second additive satisfy: X / Y=1~50.

[0011] Optionally, the non-aqueous electrolyte satisfies at least one of the following conditions: (1) The conductivity of the non-aqueous electrolyte at 25°C is 7 mS / cm~12 mS / cm; (2) The viscosity of the non-aqueous electrolyte at 25°C is 2.0 mPa·s to 6 mPa·s.

[0012] Optionally, the non-aqueous electrolyte is not a precursor to a gel electrolyte or a polymer electrolyte.

[0013] On the other hand, the present invention provides a secondary battery, including a positive electrode, a negative electrode, and a non-aqueous electrolyte as described above.

[0014] According to the non-aqueous electrolyte provided by the present invention, compounds shown in structural formula 1 and / or structural formula 2 are added as first additives. The first additives can participate in the formation of a solid electrolyte interfacial film on the surface of the positive and negative electrodes, making the solid electrolyte interfacial film more dense and stable. This solid electrolyte interfacial film can provide better protection for the positive and negative electrodes and the non-aqueous electrolyte, and improve the cycle stability of the battery. However, the inventors have found that during long-term storage, organic peroxides and azo compounds can lead to an increase in the acidity and color of the electrolyte, deteriorating the quality of the electrolyte and affecting its application in lithium-ion batteries. This is because the first additives will produce alcohols containing active hydrogen during high-temperature storage, resulting in poor weather resistance and deterioration of electrochemical performance of the non-aqueous electrolyte. To solve this problem, compounds shown in structural formula 3 are further added to the non-aqueous electrolyte as second additives. The second additives have high reaction selectivity for active hydrogen, which can reduce the effect of water in the electrolyte system and active hydrogen contained in the positive and negative electrodes, indirectly reducing the problems of lithium salt decomposition and acidity increase caused by active hydrogen. Therefore, combining these two additives in a certain proportion can improve the weather resistance of non-aqueous electrolytes, inhibit the increase of acidity and color during storage, and at the same time take into account the room temperature cycle performance of the battery. Detailed Implementation

[0015] To make the technical problems solved, the technical solutions, and the beneficial effects of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0016] An embodiment of the present invention provides a non-aqueous electrolyte comprising a non-aqueous organic solvent, an electrolyte salt, and an additive, wherein the additive comprises a first additive and a second additive, the first additive comprising a compound represented by structural formula 1 and / or a compound represented by structural formula 2, and the second additive comprising a compound represented by structural formula 3. Structural Formula 1 Wherein, n is 0 or 1; R1 and R2 are each independently selected from hydrogen, substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C1-C12 acyl, substituted or unsubstituted C2-C12 alkoxyacyl, and substituted or unsubstituted C2-C12 ether; and R1 and R2 do not... Both are hydrogen, and R1 and R2 can be linked together to form a ring or not; R3 is selected from substituted or unsubstituted C1-C12 alkylene groups, substituted or unsubstituted C2-C12 alkenyl groups, substituted or unsubstituted C2-C12 alkyne groups, substituted or unsubstituted C6-C20 aryl groups, and substituted or unsubstituted C2-C12 ether groups; when R1, R2, and R3 are substituted, the substituents are alkoxy, hydroxyl, acyl, ester, cyano, or halogen. Structural Formula 2 R4 and R5 are each independently selected from substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C2-C6 alkenyl, substituted or unsubstituted C2-C6 alkynyl or substituted or unsubstituted C1-C6 alkyl hydroxyl groups, and R4 and R5 are linked together to form a ring or not; R6 is selected from hydrogen, substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C2-C6 alkenyl or substituted or unsubstituted C2-C6 alkynyl, C1-C6 cyano, C2-C6 ester, substituted or unsubstituted C2-C6 amide or substituted or unsubstituted C1-C6 amidine; Structural Formula 3 Wherein, m is selected from 1 to 4; R7 is selected from substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C1-C12 silyl, substituted or unsubstituted C0-C8 phosphoryl, substituted or unsubstituted C1-C10 sulfonyl.

[0017] In the non-aqueous electrolyte, the first additive can participate in the formation of the solid electrolyte interface film on the surface of the positive and negative electrodes, making the solid electrolyte interface film more dense and stable. This solid electrolyte interface film can play a good protective role for the positive and negative electrodes and the non-aqueous electrolyte, improving the cycle stability of the battery. However, the inventors found that during long-term storage, organic peroxides and azo compounds can lead to an increase in the acidity and color of the electrolyte, deteriorating the quality of the electrolyte and affecting its application in lithium-ion batteries. This is because the first additive will produce alcohols containing active hydrogen during high-temperature storage, resulting in poor weather resistance and deterioration of electrochemical performance of the non-aqueous electrolyte. To solve this problem, the compound shown in structural formula 3 is further added to the non-aqueous electrolyte as a second additive. The second additive has a high reaction selectivity for active hydrogen, which can reduce the effect of water in the electrolyte system and active hydrogen contained in the positive and negative electrodes, indirectly reducing the problems of lithium salt decomposition and acidity increase caused by active hydrogen. Therefore, combining these two additives in a certain proportion can improve the weather resistance of non-aqueous electrolytes, inhibit the increase of acidity and color during storage, and at the same time take into account the room temperature cycle performance of the battery.

[0018] In the description of this invention, the term "C1-C12 alkyl" includes straight-chain alkyl, branched alkyl, and cycloalkyl; similarly, the term "C2-C12 alkenyl" includes straight-chain alkenyl, branched alkenyl, and cycloalkenyl; the term "C2-C12 alkynyl" includes straight-chain alkynyl, branched alkynyl, and cycloalkenyl; the term "C1-C12 alkylene" includes straight-chain alkylene, branched alkylene, and cycloalkenyl; the term "C2-C12 alkenyl" includes straight-chain alkenyl, branched alkenyl, and cycloalkenyl; and the term "C2-C12 alynyl" includes straight-chain alynyl, branched alynyl, and cycloalynyl.

[0019] In the description of this invention, the term "C1-C12 acyl" should be interpreted broadly. Specifically, it can be understood as one or more carbon atoms in a C1-C12 alkyl group being surrounded by a carbonyl group. The substitution group is obtained, and the position of the substituted carbon atom is not particularly limited. In a preferred embodiment, the acyl group of C1-C12 is selected from... , where R 14 and R 15 Each is independently selected from a single bond or a C1-C11 alkyl group.

[0020] In the description of this invention, the term "C2-C12 alkoxyacyl" should be interpreted broadly. Specifically, it can be understood as a C2-C12 alkyl group in which one or more carbon atoms are... The substituted group is obtained, and the position of the substituted carbon atom is not particularly limited. In a preferred embodiment, the C2-C12 alkoxyacyl group is selected from... , where R 16 Selected from single-bonded or C1-C11 alkyl groups, R 17 Alkyl groups selected from C1-C11.

[0021] In the description of this invention, the term "C2-C12 ether group" should be interpreted broadly. Specifically, it can be understood as a connection between two adjacent carbon atoms in a C2-C12 alkyl group. The resulting groups can have one or more oxygen atoms.

[0022] In some embodiments, in the compound represented by structural formula 1, R1 is selected from hydrogen, and R2 is selected from… substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl, wherein R 10 Selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, substituted or unsubstituted C2-C11 alkynyl, and substituted or unsubstituted C6-C20 aryl.

[0023] At this point, the compound represented by structural formula 1 is a hydroperoxide or an organic peroxy acid. When the compound represented by structural formula 1 is a hydroperoxide or an organic peroxy acid, its high oxygen content can remove reducing impurities in the electrolyte in advance, reduce the amount of gas generated during formation, improve the initial coulombic efficiency, and increase the initial discharge capacity of the secondary battery.

[0024] As an example, the compound represented by structural formula 1 may be selected from the following compounds: .

[0025] In some embodiments, in the compound represented by structural formula 1, R1 and R2 are each independently selected from substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, and substituted or unsubstituted C6-C20 aryl.

[0026] At this point, the compound represented by structural formula 1 is a dialkyl peroxide. When the compound represented by structural formula 1 is a dialkyl peroxide, it is beneficial to suppress solvent molecule co-intercalation and improve the interfacial compatibility between the electrolyte and the negative electrode.

[0027] As an example, the compound represented by structural formula 1 may be selected from the following compounds: .

[0028] In some embodiments, in the compound represented by structural formula 1, R1 is selected from... R2 is selected from hydrogen, substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl, or... , where R 11 Selected from substituted or unsubstituted C1-C11 alkyl groups, substituted or unsubstituted C2-C11 alkenyl groups, substituted or unsubstituted C2-C11 alkynyl groups, substituted or unsubstituted C6-C20 aryl groups, and substituted or unsubstituted C2-C12 etheryl groups.

[0029] In some embodiments, in the compound represented by structural formula 1, R1 is selected from... R2 is selected from , where R 11 Selected from substituted or unsubstituted C1-C11 alkyl groups, substituted or unsubstituted C2-C11 alkenyl groups, substituted or unsubstituted C2-C11 alkynyl groups, substituted or unsubstituted C6-C20 aryl groups, and substituted or unsubstituted C2-C12 etheryl groups.

[0030] At this point, the compound represented by structural formula 1 is a diacyl peroxide. When the compound represented by structural formula 1 is a diacyl peroxide, in addition to improving battery cycle life, it can also decompose to form inert carbon dioxide during battery thermal runaway to dilute the explosion limits of flammable gases, which is beneficial to improving battery safety performance.

[0031] As an example, the compound represented by structural formula 1 may be selected from the following compounds: .

[0032] In some embodiments, in the compound represented by structural formula 1, R1 is selected from... R2 is selected from hydrogen, substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, and substituted or unsubstituted C6-C20 aryl, wherein R 11 Selected from substituted or unsubstituted C1-C11 alkyl groups, substituted or unsubstituted C2-C11 alkenyl groups, substituted or unsubstituted C2-C11 alkynyl groups, substituted or unsubstituted C6-C20 aryl groups, and substituted or unsubstituted C2-C12 etheryl groups.

[0033] At this point, the compound represented by structural formula 1 is a peroxy ester. When the compound represented by structural formula 1 is a peroxy ester, it can improve the wettability of the electrolyte to the electrode, reduce the ohmic internal resistance of the battery, and improve the discharge performance of the battery.

[0034] As an example, the compound represented by structural formula 1 may be selected from the following compounds: .

[0035] In some embodiments, in the compound represented by structural formula 1, R1 is selected from... , where R 12 R2 is selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, and substituted or unsubstituted C2-C11 alkynyl; R2 is selected from hydrogen, substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, and substituted or unsubstituted C6-C20 aryl or... , where R 13 Selected from substituted or unsubstituted C1-C11 alkyl groups, substituted or unsubstituted C2-C11 alkenyl groups, and substituted or unsubstituted C2-C11 alkynyl groups.

[0036] At this point, the compound represented by structural formula 1 is a peroxycarbonate or a peroxydicarbonate. When the compound represented by structural formula 1 is a peroxycarbonate or a peroxydicarbonate, it promotes lithium-ion solvation and improves lithium diffusion performance inside the battery.

[0037] As an example, the compound represented by structural formula 1 may be selected from the following compounds: .

[0038] In some embodiments, the compound represented by structural formula 1 includes one or more of the following compounds: .

[0039] It should be noted that the compound shown in Structural Formula 2 has a symmetrical structure, that is, the compound shown in Structural Formula 2 is based on left-right symmetry of -N=N-. Under the constraints of this invention, this symmetrical structure is beneficial to the function of the compound shown in Structural Formula 2. At the same time, the C connected to N needs to be sp3 hybridized to ensure the stability of the -N=N- structure.

[0040] In some embodiments, in the compound shown in Formula 2, when R4 and R5 are substituted, the substituents are carboxyl, hydroxyl, halogen, or cyano; when R6 is substituted, the substituents are hydroxyl, halogen, or alkoxy.

[0041] In some embodiments, in the compound represented by structural formula 2, R6 is selected from cyano.

[0042] In some embodiments, in the compound shown in Formula 2, R4 and R5 are each independently selected from substituted or unsubstituted C1-C6 alkyl groups.

[0043] The C1-C6 alkyl groups include methyl, ethyl, n-propyl, isopropyl, isobutyl, tert-butyl, tert-amyl, etc.

[0044] In some embodiments, the compound represented by structural formula 2 includes one or more of the following compounds: .

[0045] In some embodiments, in the compound represented by structural formula 3, when R7 is substituted, the substituent can be a hydrocarbon group, an aromatic group, an alkoxy group, or a halogen.

[0046] In some embodiments, the compound represented by structural formula 3 includes one or more of the following compounds: .

[0047] In some preferred embodiments, when R7 is substituted, the substituent is a halogen or an alkoxy group.

[0048] In some embodiments, the mass content X of the first additive is 10 to 5000 ppm based on the total mass of the non-aqueous electrolyte; In a specific embodiment, the mass content X of the first additive, based on the total mass of the non-aqueous electrolyte, can be 10ppm, 20ppm, 30ppm, 40ppm, 50ppm, 60ppm, 70ppm, 80ppm, 90ppm, 100ppm, 234ppm, 389ppm, 550ppm, 766ppm, 1001ppm, 1255ppm, 1500ppm, 1778ppm, 2000ppm, 2333ppm, 2666ppm, 3000ppm, 3333ppm, 3666ppm, 4000ppm, 4333ppm, 4666ppm, 4900ppm, 5000ppm, or a range of any two of these values.

[0049] The first additive participates in the formation of a solid electrolyte interface film on the positive and negative electrode surfaces. The solid electrolyte interface film formed by the first additive can block the direct contact between the non-aqueous electrolyte and the positive and negative electrodes, thereby reducing the decomposition and gas production of the non-aqueous electrolyte on the negative electrode surface. This is used to improve the cycle capacity retention rate and high-temperature storage performance of the secondary battery. If the content of the first additive is too low, its effect on improving the performance of the secondary battery will be limited. If the content of the first additive is too high, it will increase the probability of side reactions of the electrolyte and also degrade the storage performance of the non-aqueous electrolyte.

[0050] In some embodiments, the mass content Y of the second additive is 10 to 1000 ppm based on the total mass of the non-aqueous electrolyte.

[0051] In a specific embodiment, the mass content Y of the second additive, based on the total mass of the non-aqueous electrolyte, can be 10ppm, 20ppm, 30ppm, 40ppm, 50ppm, 87ppm, 123ppm, 189ppm, 246ppm, 301ppm, 367ppm, 422ppm, 488ppm, 555ppm, 611ppm, 677ppm, 733ppm, 799ppm, 855ppm, 911ppm, 944ppm, 966ppm, 988ppm, 1000ppm, or a range of any two of these values.

[0052] The second additive reduces the amount of active hydrogen in the electrolyte system, thereby preventing the addition of the first additive from degrading the storage performance of the non-aqueous electrolyte and extending the storage life of the non-aqueous electrolyte and the secondary battery. If the content of the second additive is too low, the improvement in the storage life of the non-aqueous electrolyte and the secondary battery will not be significant. If the content of the second additive is too high, it will increase the viscosity of the electrolyte, reduce the ion diffusion rate, and be detrimental to reducing battery impedance.

[0053] In some embodiments, the mass content X of the first additive and the mass content Y of the second additive satisfy: X / Y = 1~50.

[0054] In a specific embodiment, X / Y can be 1, 3, 7, 10, 14, 18, 21, 25, 28, 32, 35, 38, 41, 43, 45, 46, 47, 48, 49, 50, or a range of any two of these values.

[0055] Due to the synergistic effect of the second additive and the first additive, the second additive can inhibit the degradation of the non-aqueous electrolyte by the active hydrogen generated by the first additive, thereby improving the storage performance and cycle performance of the battery. Through extensive research, the inventors discovered that when the mass content X of the first additive and the mass content Y of the second additive satisfy the condition X / Y = 1~50, the synergistic effect of the first additive and the second additive can be fully utilized, significantly extending the storage life of the non-aqueous electrolyte and the secondary battery, and improving the cycle performance of the secondary battery.

[0056] In a preferred embodiment, the mass content X of the first additive is 100~2000 ppm based on the total mass of the non-aqueous electrolyte.

[0057] In a preferred embodiment, the mass content Y of the second additive is 50~500 ppm based on the total mass of the non-aqueous electrolyte.

[0058] In a preferred embodiment, the mass content X of the first additive and the mass content Y of the second additive satisfy: X / Y = 2~20.

[0059] In this invention, the quantitative testing of the content of each component in the non-aqueous electrolyte can be performed by: diluting the non-aqueous electrolyte, detecting each component by gas chromatography (GC) or high-performance liquid chromatography (HPLC), and then calculating the retention rate of each component in the non-aqueous electrolyte. It should be noted that GC and HPLC are common component quantification techniques in the field, and the appropriate method should be selected based on the actual testing conditions.

[0060] In some embodiments, the non-aqueous electrolyte satisfies at least one of the following conditions: (1) The conductivity of the non-aqueous electrolyte at 25°C is 7 mS / cm~12 mS / cm; (2) The viscosity of the non-aqueous electrolyte at 25°C is 2.0 mPa·s to 6 mPa·s.

[0061] In a specific embodiment, the conductivity of the non-aqueous electrolyte at 25°C is a range consisting of any two of the following values: 7 mS / cm, 8 mS / cm, 9 mS / cm, 10 mS / cm, 11 mS / cm, and 12 mS / cm.

[0062] In a preferred embodiment, the conductivity of the non-aqueous electrolyte at 25°C is 8 mS / cm to 11 mS / cm.

[0063] The conductivity of the non-aqueous electrolyte at 25°C was measured using a conductivity meter.

[0064] The conductivity of the non-aqueous electrolyte is mainly affected by the combined effects of ion concentration, solvent polarity, and electrolyte viscosity. The conductivity of the electrolyte can be controlled by adjusting the ratio of lithium salt to solvent in the electrolyte.

[0065] The film-forming reaction of the first additive on the positive and negative electrode surfaces is closely related to the conductivity of the non-aqueous electrolyte. The conductivity affects the degree of battery charging polarization during the formation process. When the electrolyte conductivity is high, the diffusion rate of lithium ions in the electrolyte is fast, and the lower the degree of polarization, the better the formation effect. Therefore, controlling the conductivity of the non-aqueous electrolyte within the above range can further fully utilize the synergistic effect of the first and second additives, significantly extend the storage life of the non-aqueous electrolyte and the secondary battery, and improve the cycle performance of the secondary battery. If the conductivity of the non-aqueous electrolyte is too high, excessive ion content may lead to accelerated corrosion of the interface or materials.

[0066] In a specific embodiment, the viscosity of the non-aqueous electrolyte at 25°C can be 2.0 mPa·s, 2.3 mPa·s, 2.5 mPa·s, 2.6 mPa·s, 2.9 mPa·s, 3.0 mPa·s, 3.3 mPa·s, 3.6 mPa·s, 3.9 mPa·s, 4.0 mPa·s, 4.3 mPa·s, 4.6 mPa·s, 4.9 mPa·s, 5.0 mPa·s, 5.2 mPa·s, 5.3 mPa·s, 5.6 mPa·s, 5.9 mPa·s, 6.0 mPa·s, or any combination of these values.

[0067] In a preferred embodiment, the viscosity of the non-aqueous electrolyte at 25°C is 2.5 mPa·s to 5.2 mPa·s.

[0068] The viscosity of the non-aqueous electrolyte at 25°C was measured using a viscometer.

[0069] Viscosity of non-aqueous electrolytes is a parameter describing the frictional forces and resistance between fluid molecules. Essentially, it reflects the result of molecular thermal motion; the lower the viscosity, the faster the molecular thermal motion, and the faster the diffusion of ions and other substances in the electrolyte. This characteristic of viscosity is essentially related to factors such as van der Waals forces and other interactions between the molecules of the fluid components, as well as the frequency of molecular thermal collisions. When the viscosity of the non-aqueous electrolyte is within the above-mentioned range, it is beneficial for the interaction with saturated carbonates and lithium ions, promoting lithium ion diffusion and the participation of the first additive in the electrode coating process.

[0070] The viscosity of the non-aqueous electrolyte at 25°C can be controlled, for example, by adjusting the non-aqueous solvent and lithium salt. More specifically, the viscosity of the electrolyte can be controlled to a lower value by mixing a low-viscosity solvent and / or a high-polarity solvent, by using a low-viscosity solvent with high polarity, by using a higher content of lithium salt, or by using a lithium salt with high dissociation ability.

[0071] It is important to emphasize that the non-aqueous electrolyte is not a precursor to a gel electrolyte or polymer electrolyte, nor is it suitable as a precursor to a gel electrolyte or polymer electrolyte. The reason is that the improvement of the electrochemical performance of the secondary battery in this application relies on the compounds shown in Structural Formula 1 and Structural Formula 2 participating in the formation of the solid electrolyte interphase (SEI) film on the negative electrode surface during the battery charge-discharge formation stage, and the compounds shown in Structural Formula 1 and Structural Formula 2 remaining in the electrolyte continuously repairing the damaged solid electrolyte interphase (SEI) film during long-term battery cycling. However, as precursors to gel electrolytes or polymer electrolytes, they undergo a polymerization reaction to form a gel electrolyte before battery charge-discharge formation. In this polymerization reaction, the compounds shown in Structural Formula 1 and Structural Formula 2 act as initiators and react with polymerizable monomers, leading to the consumption of the compounds shown in Structural Formula 1 and Structural Formula 2, thus preventing them from playing their corresponding roles in charge-discharge formation and battery charge-discharge cycling.

[0072] In some embodiments, the non-aqueous electrolyte does not contain other polymerizable monomers and / or prepolymers obtained by polymerizing other polymerizable monomers, except for the second additive.

[0073] It should be noted that, although the second additive contains isocyanate groups in this application, it is not used as a polymerization monomer. On the contrary, if it is used as a polymerization monomer, its isocyanate will react and polymerize during the polymerization process, thus losing its inhibitory effect on the active hydrogen generated by the first additive during the secondary battery storage process.

[0074] In some embodiments, the other polymerizable monomers include one or more of the following: acrylate monomers (such as methyl acrylate, ethyl acrylate, butyl acrylate), acrylamide monomers (such as acrylamide, N,N'-methylenebisacrylamide), vinyl compound monomers (such as polyvinyl alcohol, vinylpyrrolidone, vinylimidazole), epoxy resin monomers (such as bisphenol A epoxy resin), polyethylene oxide monomers, polyacrylonitrile monomers, and siloxane monomers.

[0075] In some embodiments, the non-aqueous electrolyte does not undergo polymerization under light or heating conditions.

[0076] In some embodiments, the non-aqueous electrolyte does not gel or solidify under light or heating conditions.

[0077] In some embodiments, the non-aqueous electrolyte is in a liquid state after formation.

[0078] In some embodiments, the additive further includes at least one of sulfonyl lactones, cyclic carbonates, phosphates, nitriles, lithium salts, or alkanes.

[0079] In some embodiments, the sulfonyl lactone compound includes at least one of 1,3-propanesulfonyl lactone, 1,4-butanesulfonyl lactone, 1,3-propenesulfonyl lactone, and methylene disulfonate.

[0080] In some embodiments, the cyclic carbonate compound includes at least one of vinylene carbonate, ethylene ethylene carbonate, methylene ethylene carbonate, or the compound shown in structural formula 3: Structural Formula 3 In some embodiments, in structural formula 3, R 21 R 22 R 23 R 24 R 25 R 26 Each is independently selected from one of the following: hydrogen atom, halogen atom, or C1-C5 group.

[0081] In some embodiments, the phosphate ester compound includes the compound shown in structural formula 4: Structural Formula 4 In structural formula 4, R 31 R 32 R 33 Each is independently selected from C1-C5 saturated hydrocarbon groups, C1-C5 unsaturated hydrocarbon groups, C1-C5 haloalkyl groups, C6-C12 aryl groups, C6-C12 haloaryl groups, -Si(C m H 2m+1 )3, where m is a natural number from 1 to 3.

[0082] In a preferred embodiment, the phosphate ester compound represented by structural formula 4 may be at least one of the following: triphenyl phosphate, trimethyl phosphate, triethyl phosphate, triargylpropyl phosphate, diargylpropyl methyl phosphate, diargylpropyl ethyl phosphate, diargylpropyl propyl phosphate, diargylpropyl-2,2,2-trifluoroethyl phosphate, diargylpropyl-3,3,3-trifluoropropyl phosphate, diargylpropyl hexafluoroisopropyl phosphate, triallyl phosphate, diallyl methyl phosphate, diallyl ethyl phosphate, diallyl propyl phosphate, diallyl trifluoromethyl phosphate, diallyl-2,2,2-trifluoroethyl phosphate, diallyl-3,3,3-trifluoropropyl phosphate, and diallyl hexafluoroisopropyl phosphate.

[0083] In some embodiments, the nitrile compound includes at least one selected from succinic anionyl nitrile, glutaronitrile, hexanetrionitrile, adiponitrile, heptacyanide, octadionitrile, nonadionitrile, and sebaconitrile.

[0084] In some embodiments, the lithium salt additive includes at least one of lithium difluorooxalate borate, lithium bis(oxalate borate), lithium difluorophosphate, lithium tetrafluorophosphate, lithium difluorosulfonylimide, lithium bis(trifluoromethanesulfonylimide), lithium bis(pentafluoroethylsulfonylimide), lithium trifluoromethanesulfonate, lithium monofluorosulfonate, lithium tri(oxalate phosphate), lithium difluorodi(oxalate phosphate), lithium tetrafluorooxalate phosphate, lithium dicyandiamide, or lower aliphatic carboxylic acids having four or fewer carbon atoms.

[0085] In some embodiments, the alkane compound includes at least one selected from cyclopentane, cyclohexane, cycloheptane, methylcyclopentane, ethylcyclopentane, 1,3-dimethylcyclopentane, 1,4-dimethylcyclopentane, methylcyclohexane, ethylcyclohexane, propylcyclohexane, butylcyclohexane, pentylcyclohexane, cis-1-methyl-3-ethylcyclohexane, trans-1-methyl-3-ethylcyclohexane, 1,3-dimethylcyclohexane, 1,4-dimethylcyclohexane, 1,3,5-trimethylcyclohexane, and perfluoro(ethylcyclohexane).

[0086] In other embodiments, the additive may also include other additives that can improve battery performance: for example, additives that improve battery safety performance, such as flame retardant additives like fluorophosphates and cyclophosphonitriles, or overcharge prevention additives like tert-amylbenzene and tert-butylbenzene.

[0087] It should be noted that, unless otherwise specified, the content of any optional substance in the additive in the non-aqueous electrolyte is generally less than 10%, preferably 0.01-5%, and more preferably 0.1% to 2%. Specifically, the content of any optional substance in the additive can be 0.01%, 0.05%, 0.08%, 0.1%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 7.8%, 8%, 8.5%, 9%, 9.5%, 10%, or any combination of these values.

[0088] In some embodiments, the additive includes fluoroethylene carbonate, and the content of fluoroethylene carbonate is 0.01% to 30% based on 100% of the total mass of the non-aqueous electrolyte.

[0089] In some embodiments, the mass content of the non-aqueous organic solvent is 65% to 90% based on the total mass of the non-aqueous electrolyte being 100%.

[0090] Specifically, based on the total mass of the non-aqueous electrolyte as 100%, the mass content of the non-aqueous organic solvent can be 65%, 68%, 71%, 74%, 76%, 78%, 79%, 80%, 81.5%, 82%, 84%, 85%, 86%, 87%, 89%, 90%, or any combination of these values.

[0091] In some embodiments, the non-aqueous organic solvent includes at least one of ether solvents, nitrile solvents, carbonate solvents, carboxylic acid ester solvents, and sulfone solvents.

[0092] In some embodiments, the ether solvent includes cyclic ethers or chain ethers, preferably chain ethers with 3 to 10 carbon atoms and cyclic ethers with 3 to 6 carbon atoms. The cyclic ethers may specifically include, but are not limited to, at least one of 1,3-dioxane, 1,4-dioxane, crown ethers, tetrahydrofuran, 2-methyltetrahydrofuran, and 2-trifluoromethyltetrahydrofuran. The chain ethers may specifically include, but are not limited to, dimethoxymethane, diethoxymethane, ethoxymethoxymethane, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol di-n-propyl ether, ethylene glycol di-n-butyl ether, and diethylene glycol dimethyl ether. Because chain ethers have high solvation ability with lithium ions and can improve ion dissociation, dimethoxymethane, diethoxymethane, and ethoxymethoxymethane, which have low viscosity and can impart high ionic conductivity, are particularly preferred. Ether compounds can be used alone or in any combination and ratio of two or more. There are no special restrictions on the content of ether compounds. It can be arbitrary within the range that does not significantly impair the effect of the high-pressure lithium-ion battery of the present invention. When the volume ratio of non-aqueous solvent is 100%, the volume ratio is usually 1% or more, preferably 2% or more, and more preferably 3% or more. In addition, the volume ratio is usually 30% or less, preferably 25% or less, and more preferably 20% or less.

[0093] In some embodiments, the nitrile solvent may be, but is not limited to, at least one of acetonitrile, glutaronitrile, and malononitrile.

[0094] In some embodiments, the carbonate solvent includes cyclic carbonates or chain carbonates. Cyclic carbonates may specifically include, but are not limited to, at least one of ethylene carbonate, propylene carbonate, γ-butyrolactone, and butylene carbonate; chain carbonates may specifically include, but are not limited to, at least one of dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, and dipropyl carbonate. The content of cyclic carbonates is not particularly limited and is arbitrary within a range that does not significantly impair the performance of the lithium-ion battery of this invention. However, when using only one type, its lower limit relative to the total volume of the non-aqueous electrolyte solvent is typically 3% or more, preferably 5% or more. By setting this range, a decrease in conductivity due to a decrease in the dielectric constant of the non-aqueous electrolyte can be avoided, making it easier to achieve good high-current discharge characteristics, stability relative to the negative electrode, and cycle characteristics of the non-aqueous electrolyte battery. Furthermore, the upper limit is typically 90% or less, preferably 85% or less, and more preferably 80% or less. By setting this range, the oxidation / reduction resistance of the non-aqueous electrolyte can be improved, thereby contributing to improved stability during high-temperature storage. The content of the chain carbonate is not particularly limited, but relative to the total amount of solvent in the non-aqueous electrolyte, it is typically 15% or more by volume, preferably 20% or more, and more preferably 25% or more. Furthermore, it is typically 90% or less by volume, preferably 85% or less, and more preferably 80% or less. By keeping the content of the chain carbonate within the above range, it is easy to achieve an appropriate viscosity for the non-aqueous electrolyte, suppressing the decrease in ionic conductivity, and thus helping to achieve a good range of output characteristics for the non-aqueous electrolyte battery. When using two or more chain carbonates in combination, it is sufficient to ensure that the total amount of the chain carbonate meets the above range.

[0095] In some embodiments, fluorine-containing chain carbonates (hereinafter referred to as "fluorinated chain carbonates") are also preferably used. There is no particular limitation on the number of fluorine atoms in a fluorinated chain carbonate as long as it is 1 or more, but it is generally 6 or less, preferably 4 or less. When a fluorinated chain carbonate has multiple fluorine atoms, these fluorine atoms can be bonded to the same carbon atom or to different carbon atoms. Examples of fluorinated chain carbonates include dimethyl fluorinated carbonate derivatives, methyl ethyl fluorinated carbonate derivatives, and diethyl fluorinated carbonate derivatives.

[0096] Carboxylic acid ester solvents include cyclic carboxylic acid esters and / or chain carbonates. Examples of cyclic carboxylic acid esters include at least one of γ-butyrolactone, γ-valerolactone, and δ-valerolactone. Examples of chain carbonates include at least one of methyl acetate, ethyl acetate, propyl acetate, butyl acetate, propyl propionate, and butyl propionate.

[0097] In some embodiments, the sulfone solvent includes cyclic sulfones and chain sulfones. Preferably, in the case of cyclic sulfones, it is typically a compound with 3 to 6 carbon atoms, more preferably 3 to 5 carbon atoms; in the case of chain sulfones, it is typically a compound with 2 to 6 carbon atoms, more preferably 2 to 5 carbon atoms. The content of the sulfone solvent is not particularly limited and is arbitrary within a range that does not significantly impair the performance of the lithium-ion battery of the present invention. Relative to the total amount of solvent in the non-aqueous electrolyte, it is typically 0.3% or more by volume, preferably 0.5% or more by volume, more preferably 1% or more by volume. Furthermore, it is typically 40% or less by volume, preferably 35% or less by volume, more preferably 30% or less by volume. When using two or more sulfone solvents in combination, the total amount of sulfone solvent should satisfy the above range. When the content of the sulfone solvent is within the above range, a non-aqueous electrolyte with excellent high-temperature storage stability is preferred.

[0098] In a preferred embodiment, the non-aqueous organic solvent comprises a mixture of cyclic carbonates and chain carbonates.

[0099] In some embodiments, the electrolyte salt is selected from lithium salts, including LiPF6, LiODFP, LiODFB, LiBOB, LiPO2F2, LiBF4, LiSbF6, LiAsF6, LiN(SO2F)2, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiC(SO2CF3)3, LiClO4, LiAlCl4, LiCF3SO3, LiSO3F, and Li2B. 10 Cl 10 At least one of lithium chloroborane, lithium trioxazophosphate, lithium lower aliphatic carboxylic acid having four or fewer carbon atoms, or lithium tetraphenylborate.

[0100] In some embodiments, the concentration of the lithium salt in the non-aqueous electrolyte is 0.1 mol / L to 4 mol / L. In a preferred embodiment, the concentration of the lithium salt in the non-aqueous electrolyte is 0.5 mol / L to 2.5 mol / L. Specifically, in the non-aqueous electrolyte, the concentration of the lithium salt can be 0.5 mol / L, 0.55 mol / L, 0.6 mol / L, 0.65 mol / L, 0.7 mol / L, 0.8 mol / L, 0.85 mol / L, 0.9 mol / L, 0.95 mol / L, 1.0 mol / L, 1.1 mol / L, 1.15 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, 1.45 mol / L, 1.5 mol / L, 1.6 mol / L, 1.7 mol / L, 1.8 mol / L, 1.9 mol / L, 2.0 mol / L, 2.1 mol / L, 2.2 mol / L, 2.3 mol / L, 2.4 mol / L, 2.5 mol / L, or any combination of these values.

[0101] Another embodiment of the present invention provides a secondary battery, including a positive electrode, a negative electrode, and a non-aqueous electrolyte as described above.

[0102] In some embodiments, the secondary battery is a lithium-ion battery.

[0103] In some embodiments, the positive electrode includes a positive electrode material layer, the positive electrode material layer includes a positive electrode active material, and the positive electrode active material includes one or more of the following: lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel oxide (e.g., lithium nickel oxide), lithium manganese oxide (e.g., spinel-type lithium manganese oxide, layered lithium manganese oxide, etc.), lithium iron phosphate, lithium manganese iron phosphate, lithium cobalt oxide, and doped / coated modified compounds thereof. Preferably, the positive electrode active material includes LiFe... 1-x’ M' x’ PO4, LiMn 2-y’ M y’ O4 and LiNi x Co y Mn z M 1-x-y-z At least one of O2, wherein M' is selected from at least one of Mn, Mg, Co, Ni, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, Zr, W, V or Ti, and M is selected from at least one of Fe, Co, Ni, Mn, Mg, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, Zr, W, V or Ti, and 0≤x'<1, 0≤y'≤1, 0≤y≤1, 0≤x≤1, 0≤z≤1, x+y+z≤1.

[0104] In a preferred embodiment, the positive electrode active material is selected from LiFe. 1-x’ M' x’ PO4, wherein M' is selected from at least one of Mn, Mg, Co, Ni, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, Zr, W, V, or Ti, and 0 ≤ x' < 1. The lithium-ion battery described has a high specific capacity, thereby effectively improving the battery's energy density. Furthermore, the battery's charging cut-off voltage can reach 3.8V, exhibiting a high discharge plateau and good cycle stability within a conventional voltage window. Moreover, since iron is relatively abundant and inexpensive globally, compared to rare and expensive metals such as cobalt, nickel, and manganese, using the aforementioned positive electrode active material helps reduce costs and alleviate dependence on limited resources.

[0105] In a more preferred embodiment, the positive electrode active material is selected from LiFe. 1-x’ Mn x’ PO4, where 0 ≤ x' ≤ 0.5.

[0106] In some specific embodiments, the positive electrode active material may include LiCoO2, LiFePO4, LiFe 0.4 Mn 0.6 PO4, LiMn2O4, LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.7 Co 0.1 Mn 0.2 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.8 Co 0.15 Al 0.05 O2, LiNi 0.9 Co 0.05 Mn 0.05 O2, LiNi 0.5 Co 0.2 Mn 0.2 Al 0.1 O2, LiNi 0.5 Co 0.2 Al 0.3 One or more of O2.

[0107] In some embodiments, the positive electrode material layer further includes a positive electrode binder and a positive electrode conductive agent, and the positive electrode active material, the positive electrode binder and the positive electrode conductive agent are blended to obtain the positive electrode material layer.

[0108] The positive electrode binder includes at least one of the following: polyvinylidene fluoride (PVDF), copolymers of PVDF, polytetrafluoroethylene (PTFE), copolymers of PVDF-hexafluoropropylene, copolymers of tetrafluoroethylene-hexafluoropropylene, copolymers of tetrafluoroethylene-perfluoroalkyl vinyl ethers, copolymers of ethylene-tetrafluoroethylene, copolymers of PVDF-tetrafluoroethylene, copolymers of PVDF-trifluoroethylene, copolymers of PVDF-trichloroethylene, copolymers of PVDF-fluorinated vinylidene, copolymers of PVDF-hexafluoropropylene-tetrafluoroethylene, thermoplastic polyimide, polyethylene, and polypropylene; acrylic resins; and styrene-butadiene rubber.

[0109] The positive electrode conductive agent includes at least one of conductive carbon black, conductive carbon spheres, conductive graphite, conductive carbon fiber, carbon nanotubes, graphene, or reduced graphene oxide.

[0110] In some embodiments, the positive current collector comprises a metallic material capable of conducting electrons. Preferably, the positive current collector comprises at least one of Al, Ni, tin, copper, and stainless steel. In a more preferred embodiment, the positive current collector is selected from aluminum foil.

[0111] In some embodiments, the negative electrode includes a negative electrode material layer, the negative electrode material layer includes a negative electrode active material, and the negative electrode active material includes at least one of carbon-based negative electrode, silicon-based negative electrode, tin-based negative electrode, and lithium negative electrode. The carbon-based negative electrode may include graphite, hard carbon, soft carbon, graphene, mesophase carbon microspheres, etc.; the silicon-based negative electrode may include silicon materials, silicon oxides, silicon-carbon composite materials, and silicon alloy materials, etc.; the tin-based negative electrode may include tin, tin-carbon, tin oxide, and tin metal compounds; the lithium negative electrode may include metallic lithium or lithium alloys. Specifically, the lithium alloy may be at least one of lithium-silicon alloy, lithium-sodium alloy, lithium-potassium alloy, lithium-aluminum alloy, lithium-tin alloy, and lithium-indium alloy.

[0112] In a more preferred embodiment, the negative electrode active material includes at least one of graphite, hard carbon, soft carbon, graphene, and silicon-carbon composite materials.

[0113] In some embodiments, the silicon material is one or more of silicon nanoparticles, silicon nanowires, silicon nanotubes, silicon thin films, 3D porous silicon, and hollow porous silicon.

[0114] In some embodiments, the negative electrode further includes a negative electrode current collector, and the negative electrode material layer covers the surface of the negative electrode current collector. The negative electrode current collector includes a metallic material capable of conducting electrons. Preferably, the negative electrode current collector includes at least one of Al, Ni, tin, copper, and stainless steel. In a more preferred embodiment, the negative electrode current collector is selected from copper foil.

[0115] In some embodiments, the negative electrode material layer further includes a negative electrode binder and a negative electrode conductive agent, and the negative electrode active material, the negative electrode binder and the negative electrode conductive agent are blended to obtain the negative electrode material layer.

[0116] The negative electrode binder includes at least one of the following: polyvinylidene fluoride (PVDF), copolymers of PVDF, polytetrafluoroethylene (PTFE), copolymers of PVDF-hexafluoropropylene, copolymers of tetrafluoroethylene-hexafluoropropylene, copolymers of tetrafluoroethylene-perfluoroalkyl vinyl ethers, copolymers of ethylene-tetrafluoroethylene, copolymers of PVDF-tetrafluoroethylene, copolymers of PVDF-trifluoroethylene, copolymers of PVDF-trichloroethylene, copolymers of PVDF-fluorinated vinylidene, copolymers of PVDF-hexafluoropropylene-tetrafluoroethylene, thermoplastic polyimide, polyethylene, and polypropylene; acrylic resins; and styrene-butadiene rubber.

[0117] The negative electrode conductive agent includes at least one of conductive carbon black, conductive carbon spheres, conductive graphite, conductive carbon fiber, carbon nanotubes, graphene, or reduced graphene oxide.

[0118] In some embodiments, the secondary battery further includes a separator located between the positive electrode and the negative electrode.

[0119] The diaphragm can be a conventional diaphragm, such as a ceramic diaphragm, a polymer diaphragm, a non-woven fabric, or an inorganic-organic composite diaphragm, including but not limited to single-layer PP (polypropylene), single-layer PE (polyethylene), double-layer PP / PE, double-layer PP / PP, and triple-layer PP / PE / PP diaphragms.

[0120] The present invention will be further illustrated by the following examples.

[0121] Table 1 Example 1 This embodiment illustrates the preparation method of the non-aqueous electrolyte disclosed in this invention, including the following steps: Non-aqueous organic solvents ethylene carbonate (EC), propylene carbonate (PC), and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 6:1:13. Then, 1 mol / L lithium hexafluorophosphate (LiPF6) was added as an electrolyte salt. After the electrolyte salt was dissolved, 3 wt% vinylene carbonate (VC), 0.5 wt% methanedisulfonate (MMDS), 2.5 wt% fluorobenzene (FB), and the first and second additives in the mass percentages shown in Table 1 were added sequentially. After shaking and homogenization, the mixture was allowed to stand to obtain a non-aqueous electrolyte.

[0122] Examples 2-44 Examples 2-44 illustrate the non-aqueous electrolyte for lithium-ion batteries and its preparation method disclosed in this invention, including most of the operational steps in Example 1, with the following differences: In the preparation steps of the non-aqueous electrolyte: Based on the total mass of the non-aqueous electrolyte being 100%, the non-aqueous electrolyte is added to the components with the mass percentages shown in Examples 2 to 44 of Table 1.

[0123] Comparative Examples 1-33 Comparative Examples 1-33 are used to illustrate the non-aqueous electrolyte for lithium-ion batteries and its preparation method disclosed in this invention, including most of the operational steps in Example 1, with the following differences: In the preparation steps of the non-aqueous electrolyte: Based on the total mass of the non-aqueous electrolyte being 100%, the non-aqueous electrolyte is added to the components with the mass percentages shown in Comparative Examples 1 to 33 in Table 1.

[0124] Performance testing The non-aqueous electrolytes prepared in Examples 1-44 and Comparative Examples 1-33 were stored at a constant temperature of 35°C for 7 days. The acidity and color of the non-aqueous electrolytes before and after storage were measured. Acidity was calculated using acid-base titration, and color was measured directly using a colorimeter. The acidity growth rate and color before and after storage were recorded in Table 2. The acidity growth rate (%) = (acidity of electrolyte after storage - acidity of electrolyte before storage) / acidity of electrolyte before storage × 100%.

[0125] Table 2 The test results of Examples 1-44 and Comparative Examples 1-33 show that the long-term storage performance of the non-aqueous electrolyte is significantly improved after introducing the compound shown in Structural Formula 3 as the second additive into the non-aqueous electrolyte containing the first additive. Compared with the non-aqueous electrolyte without the second additive, its acidity and color increased significantly after high-temperature storage. This indicates that the second additive has high reactivity selectivity for active hydrogen, can effectively reduce the moisture in the electrolyte system, and weaken the effect of active hydrogen in the positive and negative electrodes, thereby indirectly reducing the problems of lithium salt decomposition and acidity increase caused by active hydrogen. This ensures that the non-aqueous electrolyte can maintain its stable properties after long-term storage and avoids quality deterioration caused by long-term storage.

[0126] The test results from Examples 6-10 and Examples 24-28 show that when the content of the second additive is fixed, the acidity and color of the non-aqueous electrolyte increase with the gradual increase of the content of the first additive. This indicates that the increase in acidity and color of the non-aqueous electrolyte during storage is closely related to the addition of the first additive. Furthermore, the test results from Examples 1-5 and Examples 19-23 show that when the content of the first additive is constant, the inhibitory effect on the increase in acidity and color of the non-aqueous electrolyte is significantly enhanced with the increase of the content of the second additive, further confirming that the second additive can effectively inhibit the active hydrogen generated by the first additive.

[0127] The test results of Examples 37-44 and Comparative Examples 18-33 show that different combinations of the first additive and the second additive can inhibit the increase of acidity and color in the non-aqueous electrolyte to varying degrees. This is of positive significance for improving the storage performance of the non-aqueous electrolyte after adding the first additive.

[0128] Examples 45-88 Examples 45-88 illustrate the preparation method of the lithium-ion battery disclosed in this invention, including the following steps: 1) Electrolyte Examples 45-88 respectively used the non-aqueous electrolyte of Examples 1-45 after being stored at 35°C for 7 days.

[0129] 2) Cell fabrication In a glove box with a water content <10ppm and an oxygen content <50ppm, the above electrolyte was injected into a lithium iron phosphate / graphite cell and maintained under a vacuum of 20 kPa for 10 minutes. The packaged battery was then aged at 45°C for 48 hours. Then, the first charge was performed using the following conventional formation process: 0.05C constant current charging for 2 hours, 0.1C constant current charging for 1 hour, 0.2C constant current charging for 1 hour, and resting for 24 hours. After formation, the battery was vacuumed, vented, and sealed. It was then further charged at 0.2C constant current to 3.65V, and then charged at a constant voltage to 0.03C cutoff. Finally, it was discharged at 0.2C constant current to 2.5V to obtain a secondary battery.

[0130] Examples 89-99 Examples 89-99 illustrate the non-aqueous electrolyte for lithium-ion batteries and its preparation method disclosed in this invention, including most of the operational steps in Example 45, with the following differences: The composition of the solvent in the non-aqueous electrolyte is shown in Table 4.

[0131] Examples 100-110 Examples 100-99 illustrate the non-aqueous electrolyte for lithium-ion batteries and its preparation method disclosed in this invention, including most of the operational steps in Example 63, with the following differences: The composition of the solvent in the non-aqueous electrolyte is shown in Table 5.

[0132] Comparative Examples 34-66 Comparative Examples 34-66 are used to illustrate the preparation method of the lithium-ion battery disclosed in this invention, including most of the operation steps in Example 45, the difference being: Comparative Examples 34 to 66 were prepared using non-aqueous electrolytes from Comparative Examples 1 to 33 that had been stored at 35°C for 7 days.

[0133] Performance testing The lithium-ion batteries prepared above were subjected to the following performance tests: (1) Battery room temperature cycle test: The lithium-ion battery was placed at room temperature and charged at a constant current and constant voltage of 1C to 3.65V (cutoff current 0.05C). After a short rest, it was discharged at a constant current of 1C to 2.5V, and the discharge capacity C1 was recorded. After a short rest, it was cycled 2000 times using the same charge and discharge steps, and the discharge capacity C2 of the last cycle was recorded. Cycle capacity retention (%) = C2 / C1 × 100%.

[0134] (2) Battery high-temperature storage test: The lithium-ion battery was placed at room temperature and charged to 3.65V at a constant current and constant voltage of 0.5C (cutoff current 0.05C). After a short rest, it was discharged to 2.5V at a constant current of 0.5C, and the discharge capacity D1 was recorded. After a short rest, it was charged to 3.65V at a constant current and constant voltage of 0.5C, allowed to stand for 5 minutes, and then stored at 60℃ for 45 days. The battery was then placed at room temperature and discharged to 2.5V at a constant current of 0.5C, and the discharge capacity D2 was recorded. Calculate the capacity using the following formula: High-temperature storage capacity retention rate (%) = D2 / D1 × 100%.

[0135] 1. The test results obtained from Examples 45-88 and Comparative Examples 34-66 are filled in Table 3. Table 3 The test results from Examples 45-88 and Comparative Examples 34-66 show that when non-aqueous electrolytes are stored at high temperatures for 7 days and then applied to lithium-ion batteries, those containing both the first and second additives exhibit superior performance in improving the cycle capacity retention and high-temperature storage capacity retention of lithium-ion batteries. In contrast, non-aqueous electrolytes containing only the first additive, while also showing some improvement to lithium-ion batteries, do not show significant results. Particularly noteworthy is that, even with increased content of the first additive, the cycle performance and high-temperature storage performance of lithium-ion batteries do not significantly improve without the addition of the second additive. This indicates that the negative effects of the active hydrogen produced by the first additive precisely offset its beneficial effects on the battery. However, when the second additive is added, the improvement in the electrochemical performance of the lithium-ion battery by the first additive becomes very significant. Furthermore, based on the test results in Table 2, it can be seen that the cycle capacity retention rate and high-temperature storage capacity retention rate of lithium-ion batteries are significantly correlated with the color and acidity of the non-aqueous electrolyte. This means that suppressing the increase of acidity and color of the non-aqueous electrolyte is of positive significance for improving the cycle performance and storage performance of lithium-ion batteries.

[0136] The test results of Examples 45-49 and 51-54 show that, compared with Examples 50 and 55-57, when the mass content X of the first additive and the mass content Y of the second additive meet the condition X / Y = 1 to 50, the first additive and the second additive can fully exert their synergistic effect, which can not only significantly extend the storage life of the non-aqueous electrolyte and the secondary battery, but also effectively improve the cycle performance of the secondary battery. Similarly, the same conclusion can be drawn from the test results of Examples 19-31.

[0137] 2. The test results of Examples 45 and 89-99 are entered into Table 4 (Table 4 also tests the conductivity, acidity growth rate, and color before and after storage of the corresponding non-aqueous electrolyte).

[0138] Table 4 Note: Ethyl acetate (EA), methyl propionate (MP), ethyl propionate (EP) The test results of Examples 45 and 89-99 show that when the first additive is selected from the compound shown in Structural Formula 1, controlling the solvent combination to make the conductivity of the non-aqueous electrolyte between 7mS / cm and 12mS / cm is beneficial to improving the battery cycle capacity retention rate and high-temperature storage capacity retention rate of lithium-ion batteries. This indicates that the conductivity of the non-aqueous electrolyte is related to the film formation quality of the first additive on the positive and negative electrodes, and also affects the corrosion rate of the interface and materials. When the conductivity of the non-aqueous electrolyte is controlled within a suitable range, it is beneficial to promote the uniformity of film formation on the positive and negative electrode surfaces, while avoiding corrosion problems.

[0139] 3. The test results of Examples 63 and 100-110 are entered into Table 5 (Table 5 also tests the conductivity, acidity growth rate, and color before and after storage of the corresponding non-aqueous electrolyte).

[0140] Table 5 The test results of Examples 63 and 100-110 show that when the first additive is selected from the compound shown in Structural Formula 2, controlling the solvent combination to make the conductivity of the non-aqueous electrolyte between 7mS / cm and 12mS / cm is beneficial to improving the battery cycle capacity retention rate and high-temperature storage capacity retention rate of lithium-ion batteries. This indicates that the conductivity of the non-aqueous electrolyte is related to the film formation quality of the first additive on the positive and negative electrodes, and also affects the corrosion rate of the interface and materials. When the conductivity of the non-aqueous electrolyte is controlled within a suitable range, it is beneficial to promote the uniformity of film formation on the positive and negative electrode surfaces, while avoiding corrosion problems.

[0141] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A non-aqueous electrolyte, characterized in that, It includes non-aqueous organic solvents, electrolyte salts, and additives, wherein the additives include a first additive and a second additive, the first additive including compounds shown in structural formula 1 and / or compounds shown in structural formula 2, and the second additive including compounds shown in structural formula 3; Structural Formula 1 Wherein, n is 0 or 1; R1 and R2 are each independently selected from hydrogen, substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C1-C12 acyl, substituted or unsubstituted C2-C12 alkoxyacyl, and substituted or unsubstituted C2-C12 ether; and R1 and R2 do not... Both are hydrogen, and R1 and R2 can be linked together to form a ring or not; R3 is selected from substituted or unsubstituted C1-C12 alkylene groups, substituted or unsubstituted C2-C12 alkenyl groups, substituted or unsubstituted C2-C12 alkyne groups, substituted or unsubstituted C6-C20 aryl groups, and substituted or unsubstituted C2-C12 ether groups; when R1, R2, and R3 are substituted, the substituents are alkoxy, hydroxyl, acyl, ester, cyano, or halogen. Structural Formula 2 R4 and R5 are each independently selected from substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C2-C6 alkenyl, substituted or unsubstituted C2-C6 alkynyl or substituted or unsubstituted C1-C6 alkyl hydroxyl groups, and R4 and R5 are linked together to form a ring or not; R6 is selected from hydrogen, substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C2-C6 alkenyl or substituted or unsubstituted C2-C6 alkynyl, C1-C6 cyano, C2-C6 ester, substituted or unsubstituted C2-C6 amide or substituted or unsubstituted C1-C6 amidine; Structural Formula 3 Wherein, m is selected from 1 to 4; R7 is selected from substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C1-C12 silyl, substituted or unsubstituted C0-C8 phosphoryl, substituted or unsubstituted C1-C10 sulfonyl.

2. The non-aqueous electrolyte according to claim 1, characterized in that, The compound represented by structural formula 1 satisfies at least one of the following conditions: (1) R1 is selected from hydrogen, and R2 is selected from hydrogen. substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl, wherein R 10 Selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, substituted or unsubstituted C2-C11 alkynyl, and substituted or unsubstituted C6-C20 aryl; (2) R1 and R2 are each independently selected from substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, or substituted or unsubstituted C6-C20 aryl. (3) R1 is selected from R2 is selected from substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl, or... , where R 11 Selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, substituted or unsubstituted C2-C11 alkynyl, substituted or unsubstituted C6-C20 aryl, and substituted or unsubstituted C2-C12 ether. (4) R1 is selected from , where R 12 R2 is selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, and substituted or unsubstituted C2-C11 alkynyl; R2 is selected from hydrogen, substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, and substituted or unsubstituted C6-C20 aryl or... , where R 13 Selected from substituted or unsubstituted C1-C11 alkyl groups, substituted or unsubstituted C2-C11 alkenyl groups, and substituted or unsubstituted C2-C11 alkynyl groups.

3. The non-aqueous electrolyte according to claim 1, characterized in that, The compound represented by structural formula 1 includes one or more of the following compounds: 。 4. The non-aqueous electrolyte according to claim 1, characterized in that, The compound represented by structural formula 2 satisfies at least one of the following conditions: (1) When R4 and R5 are substituted, the substituents are carboxyl, hydroxyl, halogen or cyano; when R6 is substituted, the substituents are hydroxyl, halogen or alkoxy. (2) R6 is selected from cyano; (3) R4 and R5 are each independently selected from substituted or unsubstituted C1-C6 alkyl groups.

5. The non-aqueous electrolyte according to claim 1, characterized in that, The compound represented by structural formula 2 includes one or more of the following compounds: 。 6. The non-aqueous electrolyte according to claim 1, characterized in that, The compound represented by structural formula 3 includes one or more of the following compounds: 。 7. The non-aqueous electrolyte according to claim 1, characterized in that, The non-aqueous electrolyte satisfies at least one of the following conditions: (1) The mass content X of the first additive is 10~5000 ppm based on the total mass of the non-aqueous electrolyte; (2) The mass content Y of the second additive is 10~1000ppm based on the total mass of the non-aqueous electrolyte; (3) The mass content X of the first additive and the mass content Y of the second additive satisfy: X / Y=1~50.

8. The non-aqueous electrolyte according to claim 7, characterized in that, The non-aqueous electrolyte satisfies at least one of the following conditions: (1) The conductivity of the non-aqueous electrolyte at 25°C is 7 mS / cm~12 mS / cm; (2) The viscosity of the non-aqueous electrolyte at 25°C is 2.0 mPa·s to 6 mPa·s.

9. The non-aqueous electrolyte according to claim 1, characterized in that, The non-aqueous electrolyte is not a precursor to a gel electrolyte or a polymer electrolyte.

10. A secondary battery, characterized in that, It includes a positive electrode, a negative electrode, and a non-aqueous electrolyte as described in any one of claims 1 to 9.